2019
DOI: 10.1101/19001115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting the impact of population ageing on tuberculosis incidence

Abstract: Background: Tuberculosis (TB) disease reactivates from distant latent infection or recent (re)infection. Progression risks increase with age. Across the World Health Organisation Western Pacific region, many populations are ageing and have the highest per capita TB incidence rates in older age groups. However, methods for analysing age-specific TB incidence and forecasting epidemic trends while accounting for demographic change remain limited. Methods: We applied the Lee-Carter models, which were originally … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…1C and 1E). This result is in line with other studies that found that older adults are more susceptible to falling ill, since they have a decline in immunity, as well as other comorbidities [17,27,34,37,38].…”
Section: Discussionsupporting
confidence: 92%
“…1C and 1E). This result is in line with other studies that found that older adults are more susceptible to falling ill, since they have a decline in immunity, as well as other comorbidities [17,27,34,37,38].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, women working in the informal sector need to work long hours to earn their income, not having time to respond to their health needs in a timely manner and being more likely to visit health facilities only when they are seriously ill [26].Regarding the cases of tuberculosis in the population over 59 years of age in the city of Imperatriz, the present study showed a high incidence in both genders, especially in the initial years of the study ( Figure 1D and 1G). This result is in line with other studies that found that older adults are more susceptible to falling ill, since they present a decline in immunity, as well as having other comorbidities [16,26,33,36,37].…”
Section: Discussionsupporting
confidence: 92%
“…Chu-change Ku et al [20] applied the Lee-Carter model to simulate temporal trends in age-specific TB incidence in Taiwan from 2005 to 2018, and the model predicted that elder Taiwanese TB patients will account for 78% of all TB cases by 2035 and that TB incidence will be 39% higher in 2035 than it would have been in the absence of an aging population. This shows that early adoption of TB surveillance and prevention in the elderly population is essential.…”
Section: Resultsmentioning
confidence: 99%